Educational System in Germany - Bozorova Rozigul Sharofovna; Ibadova Zamira Rashidovna (Researchparks Publishing, 2023)
Education in Germany is primarily the responsibility of the individual German states (Länder), with the federal government playing a minor role. Voluntary kindergarten (kindergarten) education is provided for all children between the ages of one and six, after which school attendance is compulsory. Overall, Germany is one of the OECD's best performing countries in reading literacy, mathematics and science, with an average student score of 515 on the PISA assessment test, well above the OECD average of 497.